"I Use All the Parts I'm Given": A Qualitative Investigation of Trans Masculine and Nonbinary Individuals' Use of Body during Sex. Issue 1 (2nd January 2021) - Anzani, Annalisa; Lindley, Louis; Prunas, Antonio; Galupo, Paz
Abstract: Objectives: The study investigates how trans masculine and nonbinary individuals describe the use of their bodies during sexual activities. Methods: Three hundred and sixty-one trans masculine and nonbinary individuals were asked to describe their use of body during sex through an online survey. Data were analyzed through thematic analysis. Results: Eleven subthemes emerged that were organized in 4 overarching themes: Relational Factors; Behavioral Factors; Sexual Roles; and Transgender Related Factors. Some differences emerged between trans masculine and nonbinary participants. Conclusions: Although some of our participants described a lack of sexual activity, our participants overall described a wide range of activities.